Physiological and performance effects of high-intensity interval training in tennis players: a systematic review - Durmus, D.; Ödemis, H.; Sögüt, M. (Coaching and Sport Science Review, 2023)
The purpose of this systematic review was to overview the physiological and performance effects of high-intensity interval training (HIIT) in tennis players. Searches for this review were performed by using four electronic databases: Web of Science, Scopus, SPORTDiscus with Full-Text, and PubMed. Intervention studies investigating the effects of HIIT on tennis players were searched from inception to December 29th, 2021. Seven studies met all of the inclusion criteria and were included in the study. The findings revealed that tennis players who participated in HIIT interventions had improved their aerobic capacity and tennis performance. Fluctuating results were reported for agility, sprint, and jump performances. In conclusion, the results of the review may suggest that HIIT is more beneficial for tennis players to achieve improvement in cardiorespiratory fitness and technical abilities regardless of age, gender, and competitive level.